非小细胞肺癌podoplanin阳性淋巴管密度与多层螺旋CT表现的关系 (Zhongguo Fei Ai Za Zhi, 2012)
BACKGROUND AND OBJECTIVE: It has been proven that ymphatic microvessel density (LMVD) was closely correlated with the lymphatic metastasis of non-small cell lung cancer (NSCLC). The aim of the present study is to explore the relationship between podoplanin-LMVD and multi-slice spiral computed tomography (MSCT) characteristics of NSCLC. METHODS: MSCT scanning was performed on 34 cases of NSCLC (squamous carcinoma, 15 cases; adenocarcinoma, 15 cases; and adenosquamous carcinoma, 4 cases) prior to operation. Clinical pathology results, including lymph node metastasis, were obtained. CT characteristics, such as shape of the edge, internal structure, and adjacent structures, were described. LMVD in the central and peripheral areas examined respectively using SP immunohistochemical technique were analyzed. RESULTS: Lymph node metastasis was found to be associated with LMVD in the peripheral areas. LMVD in the peripheral areas of the resected lesions, the MSCT findings of which included spinous process, pleural indentation, and carcinomatous lymphangitis, was higher than that of the lesions without these MSCT characteristics (P < 0.05). CONCLUSION: MSCT findings of spinous process, pleural indentation, or carcinomatous lymphangitis of NSCLC may suggest a higher level of tumor lymphangiogenesis with a higher risk of lymph node metastasis.